The Development of Classroom Action Research Teaching Materials Through the Integration of Interactive E-Books with Flipped Learning - Irna Sjafei; Dadi Waras Suhardjono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Digital learning materials for Classroom Action Research (CAR) in higher education are generally still presented as passive PDF e-books that provide limited support for self-directed learning. This condition highlights the need to develop more interactive and open-access instructional materials. The purpose of this study is to develop interactive CAR materials that are valid and feasible to support flipped learning. The development process adapted the Hannafin & Peck model, which consists of the stages of needs analysis, design, development, and systematic evaluation and revision. The needs analysis, design, and development phases primarily employed qualitative data, while the product evaluation phase used expert-validated questionnaires to ensure the relevance and validity of each item. The expert evaluation results show that the average score given by material and instructional experts, media experts, and language experts reached 97.45%, which is categorized as “excellent” and feasible for implementation. Based on these key findings, the interactive e-book developed for CAR learning materials through a flipped learning approach received an overall rating of “excellent and highly feasible,” indicating that it can be directly implemented in CAR instruction as either a primary or supplementary learning resource. As this study was limited to expert validation, further research is recommended in the form of field testing to examine the product’s effectiveness on learning outcomes, motivation, or student competence.